(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2014)
Background: Different treatment modalities and procedures have been tried for the management of infantile hypertrophic pyloric stenosis. But surgery remains the mainstay for management of IHPS. Ramstedts pyloromyotomy was described almost over a hundred years ago and to date remains the surgical technique of choice. An alternative and better technique is the double-Y pyloromyotomy, which offer better results for management of this common condition. Methods: A prospective comparative interventional study of 40 patients with IHPS was carried out over a period of 2 years from July 2008 to July 2010. The patients were divided into 2 equal groups of 20 patients in each. The study was designed that all patients selected for study were optimized preoperatively regarding to hydration, acid-base status and electrolytes imbalance. All surgeries were performed after obtaining informed consent. Standard preoperative preparation and postoperative feeding regimes were used. The patients were operated on an alternate basis, i.e., one patient by Double-Y Pyloromyotomy(DY) and the next by aRamstedts Pyloromyotomy (RP). Data on patient demographics, operative time, anesthesia complications, postoperative complications including vomiting and weight gain were collected. Patients were followed up for a period of 3 months postoperatively. Statistical assessments were done by using t test. Results: From July 2008 through July 2010, fourty patients were finally analyzed for this study. Any statistical differences were observed in patient population regarding age, sex, weight at presentation, symptoms and clinical condition including electrolytes imbalance and acid-base status were recorded. Significant differences were found in postoperative vomiting and weight gain. Data of post operative vomiting and weight gain in both groups were collected. Vomiting in double-Y(DY) pyloromyotomy group (1.21 ± 0.45days) vs Ramstedts pyloromyotomy (RP) group(3.03 ± 0.37days) p= 0.0001.Weight gain after 1st 10 days DY vs RP is ( 298 ± 57.94 gm vs193±19.8 gm p=0.0014), after 1 month (676.67±149.84 gm vs 466.67 ± 127.71 gm, p=0.0001), after 2months (741.33± 278.74 gm vs 490±80.62 gm, p=0.002) and after 3 months (582±36.01gm vs 453.33±51.64 gm, p=0.0001).No long-term complications were reported and no re-do yloromyotomy was needed. Conclusion: The double-Y pyloromyotomy seems to be a better technique for the surgical management of IHPS. It may offer a better functional outcome in term of postoperative vomiting and weight gain. DOI: http://dx.doi.org/10.3329/jpsb.v1i2.19532